ANALISA PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN (STUDI KASUS DI PT. X) - Francisca Hermawan; Yuvenny Christine (Bina Ekonomi, 2014)
One benchmark is a good resource to have good performance and one of the factors that a good performance is the provision of compensation to the employee. This study was conducted to determine whether there is a significant impact on the provision of compensation to the performance of the employee PT "X". Compensation variables used in this study is the Base Pay, Variable Pay, and Benefits. While the data used in this study of a sample questionnaire with 71 respondents. The method of data analysis used is multiple linear regression technique. The results showed that administration of compensation PT "X" has a significant influence on employee performance.